Handbook of Community Well-Being Research - Phillips, Rhonda; Wong, Cecilia (Springer Netherlands : Imprint: Springer, 2017)
This Handbook brings together foundational and leading-edge research exploring dimensions of improving quality of life in communities of place. Social indicators and other assessment techniques will be explored, including from the framework of community perspectives which is concerned with enhancing quality of life for community members. As part of this trans-disciplinary work, participation, engagement, and empowerment will be key concepts presented. Along with capacity building and service provision, these elements influence community well-being and will be considered along with subjective and objective assessment approaches. Researchers from around the globe share their work on this important topic of community well-being, bringing together a diverse array of disciplinary perspectives. Those working in the areas of public policy, community development, community and social psychology, urban and regional planning, and sustainable development will find this volume particularly useful for the array of approaches presented. .
Keywords: Social sciences.; Medical research.; Regional planning.; Urban planning.; Sustainable development.; Quality of life.; Community psychology.; Environmental psychology.; elektronické knihy; electronic books